Relevance and Consistency of Lithium Application Learning Media for High School Students on Chemical Equilibrium Material - Dewi Masyitha; Afadil Afadil (Universitas Tadulako, 2022)
Conditions of the Covid-19 pandemic require teachers and students to innovate starting from the preparation, process, and assessment of learning. This study aims to design and determine the relevance and consistency of Lithium application learning media for high school students on chemical equilibrium in the form of e-modules as a solution to reduce misconceptions. This type of research is a part of Research and Development (R&D) starting from product design to determining its theoretical relevance and consistency by experts. The product produced is in the form of an e-module on chemical balance material using Android with the Lithium application which is used by students in online learning during the Covid-19 pandemic. The instrument used was a questionnaire on the feasibility of learning media, the suitability of the material, and the Lithium application. The results of the evaluation of the media expert validator and the material expert respectively obtained the value of relevance and consistency of 3.15 (valid); 3.00 (valid); and 3.65 (very valid). This means that the Lithium application can be used as an online learning medium by utilizing Android as a solution to reduce high school students' misconceptions of chemical equilibrium material.